KARAKTERISTIK SIFAT FISIK TANAH PADA LAHAN BUDIDAYA UBI KAYU (Manihot Esculenta Crantz) DI DESA WOLOGAI TENGAH - Mariana Umin; Agustinus JP Ana Saga (Agriculture Faculty of Flores University, 2019)
Characteristics of soil physical properties are the diversity of soil conditions based on structure, texture, soil color, and soil moisture content. Features of the physical properties of the soil influenced by several factors, including poor land management, which results in a decrease in fertility levels that includes physical, chemical, and biological soil characteristics.The method used in this study is the sample cluster method. Consists of a small group of units and then randomly selected as a representative of the population, all elements in the chosen cluster used as research samples. This study aims to determine the physical characteristics of soil texture, soil structure, soil color, and soil moisture content in cassava (Manihot esculenta Crantz) in Wologai Tengah Village.The results showed that the texture of the soil in cassava soil dominated by clay texture. The structure of the angular lumpy ground, soil color 10 YR 2/1 Black, and 10 YR 2/2 Very Dark Brown and had a soil moisture content of 37.4%. This soil type is an ideal soil type or classified as fertile to cultivate cassava plants.